ATHEROSCLEROSIS AND ITS IMPACT ON HEALTH, EARLY DIAGNOSIS, PREVENTIVE MEASURES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Atherosclerosis is one of the most common chronic arterial diseases. It causes an atherosclerotic plaque of cholesterol to form in the vessel wall. These plaques narrow the lumen of the vessel, which affects blood flow, and in extreme cases, plaques can completely block the blood flow. If something like this happens in a large artery, the situation is fraught with serious complications, even death: cardiovascular diseases have been one of the main causes of death for many years. The cause of atherosclerosis is a disorder in fat metabolism - the accumulation of cholesterol (namely low-density lipoproteins) in excess.